The Effect of Fusaric Acid Application on the Lignin and Suberin Formation as Resistance Indicator on Tomato - Abdul Azis Ambar; Amiruddin Syam; Henny Setyawati; Nur Ilmi (International Journal of Agriculture System, 2015)
Fusaric acid (=FA) is a phytotoxin produced by Fusarium oxysporum, pathogen of wilt disease on tomato. A concentration of FA causes death of plant. However, low concentration will elicit various plant defense responses and inhibit pathogen growth. The research focused on the observation of lignin and suberin formation after application of FA on tomato in different concentration. This research was caried out at elementary laboratory of Agriculture Faculty of Muhammadiyah University of Parepare, Parepare and Micology Laboratory of Gadjah Mada University, Yogyakarta. Four concentrations of FA (sigma) 0, 25, 50, 75, and 100 ppm were used in this research, whereas inoculation with Fusarium oxysporum was served as control. Lignin and suberin formations in plant cell as structural resitantance response were analyzied by using microtechnique protocol. The result of histological analysis showed that treatment of F. oxysporum, 10 ppm, 50 ppm, 75 ppm, and 100 ppm of FA, caused a change in lignin content of tomato cell on 10 – 40 days after application and followed also by necrotitation. The application of 25 ppm FA increases the lignin and the suberin content without necrosis on 20 and 30 days after application.